Hyperpolarized [1, 3‐13C2]ethyl acetoacetate is a novel diagnostic metabolic marker of liver cancer. Issue 4 (4th September 2014) - Jensen, Pernille R.; Serra, Sonia Colombo; Miragoli, Luigi; Karlsson, Magnus; Cabella, Claudia; Poggi, Luisa; Venturi, Luca; Tedoldi, Fabio; Lerche, Mathilde H.
<x xml:space="preserve">Abstract</x> An increased prevalence of liver diseases such as hepatitis C and nonalcoholic fatty liver results in an augmented incidence of the most common form of liver cancer, hepatocellular carcinoma (HCC). HCC is most often found in the cirrhotic liver and it can therefore be challenging to rely on anatomical information alone when diagnosing HCC. Valuable information on specific cellular metabolism can be obtained with high sensitivity thanks to an emerging magnetic resonance (MR) technique that uses 13C labeled hyperpolarized molecules. Our interest was to explore potential new high contrast metabolic markers of HCC using hyperpolarized 13C‐MR. This work led to the identification of a class of substrates, low molecular weight ethyl‐esters, which showed high specificity for carboxyl esterases and proved in many cases to possess good properties for signal enhancement. In particular, hyperpolarized [1, 3‐13C2]ethyl acetoacetate (EAA) was shown to provide a metabolic fingerprint of HCC. Using this substrate a liver cancer implanted in rats was diagnosed as a consequence of an ∼4 times higher metabolic substrate‐to‐product ratio than in the surrounding healthy tissue, (p = 0.009). Unregulated cellular uptake as well as cosubstrate independent enzymatic conversion of EAA, made this substrate highly useful as a hyperpolarized 13C‐MR marker. This could be appreciated by the signal‐to‐noise (SNR) obtained from EAA, which was comparable to the SNR reported in a literature liver cancer study with state‐of‐the‐art hyperpolarized substrate, [1‐13C]pyruvate. Also, the contrast‐to‐noise (CNR) in the EAA based metabolic ratio images was significantly improved compared with the CNR in equivalent images reported using [1‐13C]pyruvate.